Tradisi Pemberian Kanaan dan Pemilihan dalam Kepercayaan Israel - Robi Prianto (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2015)
Tradition of awarding Canaan and elections in Israel confidence occur simultaneously. When the Israelites were brought out of the land of Egypt to the land of Canaan, at that time the people of Israel was born into humanity of God. Canaan for the Israelites is a testament to the inclusion and the presence of a God over them, so no matter the people of Israel kept the land claim and maintain Canaan as their inheritance.Therefore Israelities were failed to become humanity of God, so is God to give status humanity of God to every body without to seeing is ethnic nation, provided they to belive to Jesus Christ as God and savior.